To The Problem of Law Enforcement Legal Errors: Theoretical and Legal Aspect - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2024)
This scientific article examines controversial issues related to law enforcement errors. Attention is drawn to their concept, features, nature, and classification. Of fundamental importance is the issue of the causes of law enforcement errors. One of the conclusions of the work is that a law enforcement error is understood both as a result of a conscientious error and as a result of carelessness.